2015
DOI: 10.1039/c4cp05025h
|View full text |Cite
|
Sign up to set email alerts
|

Reversible oxygen addition on a triplet sensitizer molecule: protection from excited state depopulation

Abstract: We demonstrate that photoactivated oxygen addition to diphenylanthracene moities can be used as a tool for protection of porphyrin's phosphorescence against oxygen quenching. Phosphorescent palladium(II) tetrabenzoporphyrin, covalently linked to four diphenylanthracene moieties, was synthesized and studied. Upon irradiation with ambient light or red laser in solution in air, addition of oxygen and formation of the corresponding endoperoxides were observed. Heating of the irradiated samples afforded the parent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 93 publications
2
33
0
Order By: Relevance
“…Consequently, the majority of TTA-UC systems have been studied in solution 8,[11][12][13][14][15] or soft polymer matrices, [16][17][18][19][20] in which the TET and TTA processes are mediated by molecular diffusion and collision. Meanwhile, it is desirable for device applications that TTA-UC processes occur in the solid state without molecular diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the majority of TTA-UC systems have been studied in solution 8,[11][12][13][14][15] or soft polymer matrices, [16][17][18][19][20] in which the TET and TTA processes are mediated by molecular diffusion and collision. Meanwhile, it is desirable for device applications that TTA-UC processes occur in the solid state without molecular diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In fact, it has been already reported that singlet oxygen produced by the thermal decomposition of 2-pyridone endoperoxides lead to cell death by ap rocess resembling apoptosis in cancer cell cultures. [10] In addition, phthalocyanine [11] and porphyrin endoperoxide [12] derivatives were reported where the endoperoxides are obtained by selfphotosensitization. Thus,i ti se vident that ar ationally designed bifunctional photosensitizer/2-pyridone conjugate may be an optimal agent for an ovel approach to fractional photodynamic therapy.2 ,6-Dibromo (and iodo) distyryl BODIPY derivatives (BODIPY = boron-dipyrromethene) were shown [13][14][15][16] to be promising long-wavelength sensitizers of molecular oxygen.…”
mentioning
confidence: 99%
“…Otherwise, a supramolecular matrix should be added to the solution to isolate the phosphors from oxygen quenching . An internal scavenger for oxygen covalently bonded to the phosphors was found to slightly enhance the phosphorescence . We have also noted that a cyclometalated Pt II complex was mentioned to show enhanced emission intensity upon prolonged exposure to ambient light .…”
Section: Methodsmentioning
confidence: 99%
“…Excitation spectra by monitoring the emission intensity at 400 and 583 nm, respectively, matched well with the absorption spectrum. This indicates that the high‐ and low‐energy emissions are both derived from the same absorbing state of ligand centered ππ* transition . The vibronically progressional spacings, quantum yield, and lifetime of the 537 nm band are 2250/1360 cm −1 , 10 %, and 153 μs, respectively.…”
Section: Methodsmentioning
confidence: 99%